English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-30 13:07:15 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

im gonna split them up so its not so confusing

(x^-7)^-2 = x^14
(y^11)^-2 = y^-22
(z^14)^-2 = z^ -28

when u have a negative power, u can get rid of the negative by putting the whole thing into the denominator:

(x^14) (y^-22) (z^-28) =

(x^14) / (y^22) (z^28)

2006-10-30 13:10:28 · answer #1 · answered by Moo 4 · 0 0

(x^-7y^11z^14)^-2 = x^(2*7) * y (-2*11) * z(-14 * 2) = x^14 * y^(-22) * z(-28)

2006-10-30 21:10:28 · answer #2 · answered by James Chan 4 · 0 0

okay....this had better not be homework!!!

simplifying exponential expressions...

(x^-7)^-2 =x^14
(y^11)^-2=y^-22 or 1/(y^22)
and (z^14)^-2=z^-28 or 1/(z^28) (if i remember right, to simplify means no negative exponents)

so ~~~~~~~~~> x^14 / [y^22 * z^28]

2006-10-30 21:15:43 · answer #3 · answered by gggjoob 5 · 0 0

x^14y^-22z^-28
x^14/(y^22z^28)

2006-10-30 21:10:51 · answer #4 · answered by dla68 4 · 0 0

fedest.com, questions and answers